2019
DOI: 10.3390/nu11081936
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Isoflavone Intake and Ulcerative Colitis Symptoms in Polish Caucasian Individuals

Abstract: Currently there are contradictory observations regarding the associations between the isoflavone intake and inflammatory bowel disease in terms of its prevention and treatment, and this may be attributed to the diversity of applied doses and influence of various isoflavones. The aim of the presented cross-sectional study is to analyze the association between intake of various isoflavones (daidzein, genistein, glicytein and total isoflavones) and ulcerative colitis symptoms (fecal blood, mucus and pus) in Polis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…Taken together, it is possible to associate the anti-colitis effect observed in preclinical studies with the phytochemical content found in NCHE. To strengthen our findings, clinical studies about supplementation with flavonoids in patients with IBD have demonstrated a positive correlation in the maintenance of remissive disease status [ 59 , 60 ].…”
Section: Discussionsupporting
confidence: 62%
“…Taken together, it is possible to associate the anti-colitis effect observed in preclinical studies with the phytochemical content found in NCHE. To strengthen our findings, clinical studies about supplementation with flavonoids in patients with IBD have demonstrated a positive correlation in the maintenance of remissive disease status [ 59 , 60 ].…”
Section: Discussionsupporting
confidence: 62%
“…The study included the analysis of diet, as well as the analysis of the disease symptoms in the period of remission. The previous analysis verified the association between dietary intake of carotenoids [16,20], as well as isoflavones [17,21], and the symptoms of ulcerative colitis. However, those studies did not explain fully the influence of diet, so it was hypothesized, that there may be some other diet-related factor which may influence the disease.…”
Section: Study Proceduressupporting
confidence: 57%
“…Based on the indicated inclusion and exclusion criteria, the total number of 55 participants were recruited, while 19 males and 36 females volunteered to participate in the study. The characteristics of the studied group were presented in the previous publications, while the majority of respondents declared no more than three bowel movements per day in the period of remission [17], and the concurrent diseases did not differ between male and female respondents [18]. The demographic and clinical characteristics of the included patients are presented in Table 1.…”
Section: Study Participantsmentioning
confidence: 99%
“…[6] Thus, it is crucial to explore candidate compounds for treating UC. [7,8] Cinnamaldehyde (CIN, 3-phenylprop-2-enal, C 9 H 8 O), an active ingredient of cinnamon oils from cinnamon bark (Cinnamomum cassia; Lauraceae), has been used for centuries as a traditional medicine and flavoring agent in Eastern Asia. [9] Previous studies have shown that CIN has anti-oxidant, [10] anti-microbial, [11,12] and anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%